GAMBARAN POTENSI MASYARAKAT PENGGUNA PELAYANAN KESEHATAN TRADISIONAL DI WILAYAH KELURAHAN ROWOSARI KECAMATAN TEMBALANG KOTA SEMARANG - Mulikhatun Umamah; Anneke Suparwati; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Every human will automatically seek the efforts of healing in various ways when being illness, such as self treatment, treatment in convensional health services, or in traditional health services. Currently the traditional health services begin to exist again, with the support of the PP 103 of 2014 about the traditional health services. The result of survey in the Rowosari of Tembalang District in Semarang City which is located on the edge of the city where border on the Regency of Demak and Semarang district are still many users of traditional health services, as well as traditional health service providers in it. The purpose of this research to knows how the potential society in Rowosari as user of traditional health services. This research uses descriptive quantitative method with cross sectional approach. Samples were 93 households out of a total of 3,802 households. Univariate analysis indicate that traditional health service users in the region of Rowosari are 74.2%. the greatest number are 32.4% of users were have the range 36-45 years of age, 57% of users are women, 23.7% of users had elementary education, 39.8% of users have income under the Regional Minimum Wage. The intended use of traditional health services more as promotive-preventive. The most provider of traditional health service in Rowosari is “penyehat tradisional” where the types are jamu and massage sequence that include in empirical traditional health services type. The traditional health service providers most widely used types of empirical traditional health services, that are jamu and massage sequence. Suggested the government sosialiszation he contents and purpose of PP. No. 103 of 2014 to society immediately with the result that PP 103 of 2014 can be implemented properly.